2020
DOI: 10.1177/1362361319900839
|View full text |Cite
|
Sign up to set email alerts
|

Public knowledge and stigma of autism spectrum disorder: Comparing China with the United States

Abstract: Autism spectrum disorder in China differs considerably from autism spectrum disorder in the West in terms of prevalence estimates, education opportunities, and life outcomes of autistic people. The lack of autism spectrum disorder awareness could be a key factor underlying the disparities. To date, there has been no evaluation of autism spectrum disorder knowledge among the general public of China. Using the Autism Stigma and Knowledge Questionnaire developed for use in diverse cultural contexts, this study un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 41 publications
8
57
0
Order By: Relevance
“…The prevalence estimates of ASD in China differ significantly from those in the West, and the key factor in this difference may be the lack of awareness of ASD in China ( 18 ). Gaps in awareness and knowledge of ASD among child health care workers may lead to delays in diagnosis and intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence estimates of ASD in China differ significantly from those in the West, and the key factor in this difference may be the lack of awareness of ASD in China ( 18 ). Gaps in awareness and knowledge of ASD among child health care workers may lead to delays in diagnosis and intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Independence and autonomy are less valued in collectivist versus individualist cultures. In addition, other cultural factors, such as stigma, which exists in Western cultures ( Green, 2003 ; Kinnear et al, 2016 ; Yu et al, 2020 ) but has been reported to be particularly salient in a number of Asian cultures due to the association with shame and dishonor ( Hwang & Charnley, 2010 ; Mak & Cheung, 2008 ; Mak & Kwok, 2010 ; Zhou et al, 2018 ), may be a powerful predictor of FQOL. In confronting adversity, the concept of resilience may be valid in both Western and Korean cultures and may be potentially valuable when attempting to assess how the family navigates between personal experience with ASD and cultural beliefs about ASD ( Hwang & Charnley, 2010 ).…”
mentioning
confidence: 99%
“…Crucially, all these efforts should be grounded in a cohesive ideology that does not solely focus on impairment and deficits but recognises the strengths and potential of autistic individuals alongside the very real needs that they may have. While autism stigma is not a problem unique to Singapore (Liao et al, 2019;Yu et al, 2020), our participants' responses suggest that Singapore may be lagging behind in the global movement away from a pure medical model of disability.…”
Section: Discussionmentioning
confidence: 75%